The pattern of Electrophysiological Abnormality in Long-Standing Type-2 Diabetes Mellitus Patients: Experience at Referral Neurology Hospital in Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2021)
Background: Nerve conduction studies (NCS) are the most objective measure of nerve function, and their use is recommended in the clinical and epidemiological evaluation of diabetic polyneuropathy.Objective: This study was conducted to describe the pattern of electrophysiological abnormality in long-standing type-2 Diabetes Mellitus patients.Methodology: This cross-sectional study was conducted in the Department of Neurophysiology at the National Institute of Neurosciences & Hospital, Dhaka, Bangladesh from July 2017 to June 2019. Among the one hundred and eight consecutive patients of type 2 diabetes with a duration of more than 10 years attending the Neurophysiology laboratory, patients were selected for the study based on the inclusion and exclusion criteria. NCS study of the right upper limb (median and ulnar nerves) and left lower limbs (tibial, peroneal, and sural nerves) were done. NCS of other nerves were also done when indicated.Result: A total number of 92 patients were recruited for this study. NCS was abnormal in 56 (60.9%) patients. 43.5% (n=40) patients were male and 56.5% (n=52) patient were female. Among the 56 (60.9%) patients with abnormal NCS, most [35 (38%)] had mixed types (both sensory and motor) of neuropathy. In 28 (30.4%) patients, both demyelination and axonal involvement were present. The median nerve (46.7%) was the commonest nerve to be involved followed by the Sural nerve. In patients with elevated HbA1C, the axonal loss was more pronounced in the lower limbs’ nerves. Polyneuropathy (28.26%) was more than mononeuropathy (21.74%).Conclusion: Most of the patients of type 2 long-standing DM developed a mixed type of polyneuropathy and elevated HbA1C was significantly associated with the axonal involvement predominantly in lower limbs’ nerves.Journal of National Institute of Neurosciences Bangladesh, January 2021, Vol. 7, No. 1, pp. 10-13